Financial and Social Factors Shaping High School Students’ Career Choices - Imashev Aibek; Fatima Salkynbayeva; Azhar Kizimbayeva; Lyazzat Mukhambetova (SHS Web of Conferences)
This study investigates the key factors influencing high school students’ career choices, with a particular focus on financial compensation, professional prestige, and personal development. The primary aim is to understand how these factors, along with parental influence and available career information, shape students’ career decisions. A survey was conducted among high school students to gather insights into their motivations and preferences. Results show that the majority of students (57.4%) prioritize salary as the main motivator, followed by the profession’s social prestige (13.2%) and personal development opportunities (12.3%). Parental influence plays a significant role, with 57.2% of students acknowledging its impact on their career choices. Additionally, a gap in career information was identified, as 71.2% of students reported feeling inadequately informed about their future career options. The study also highlights a strong preference for creative work and social interaction in career preferences. These findings underscore the need for improved career guidance programs in schools to better inform students and help them make informed decisions aligned with their interests and skills. This research has important implications for educators, policymakers, and parents, urging them to provide enhanced career counseling and support for students’ career development.